Factors influencing career choice of individual in insurance industry in Malaysia / Zawani Md Johari - Md Johari, Zawani (2010)
The overwhelming development in the Malaysia’s insurance industry has generated a huge number of career opportunities in recent times. There are many career opportunities to be selected from this field such as group insurance representative, broker, insurance regulator, claims representative, pension specialist, auditor, customer service, risk manager, benefits manager, loss control expert and financial planner. However, there was some misconception who sometimes individual believe that to pursue a career in the insurance industry, must be an insurance salesperson. The perception that most professionals in the insurance industry spend their days and evenings selling policies still exist among a few of people. Even though perception was become the big obstacles in insurance industry, surprisingly, there are many individual still choose careers in insurance. This research is conduct to highlight of why people are interested to choose a career in insurance industry. Besides to determine the most factors that influenced individual which presently attached with any insurance organization in choosing career in insurance industry. 60 respondents had participated in this research. This research focuses on Intrinsic, Extrinsic and Interpersonal as variables to determine why individuals choose their career in insurance industry in Malaysia.